AN EMPIRICAL STUDY OF FACTORS INFLUENCE ERP IMPLEMENTATION ON EDUCATION SECTOR. - Bijay Kishor Shrishri Sekhar Pattanaik, Pushpendra Khandelwal (International Journal of Advanced Science and Technology, 2020)
ENTERPRISE RESOURCE PLANNING (ERP) integrates the organization irrespective of departments and geographical locations. Smooth functioning of ERP depends a lot on the organizations. Any kind of error in ERP sends the organization to back. So effectiveness using accurate IT concept is required for motivation, sales, decision making, communications and tender of raw materials. Now a days role of erp in education sector is growing at an extremely fast. Where implementation of it in the organization is key. As it is always associated with teaching, learning, feedback, library and educational database. Further ERP technique for an effective planning and control of all resources are needed certain parameters (make, ship, take,  and account for customer orders  in a manufacturing along with distribution or service company) to realize and ideal education system. To envisage the same, many types of information systems including   different functions,  and business process have been focused in different organization now a days.